The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1010428317705744
|View full text |Cite
|
Sign up to set email alerts
|

Moschamine inhibits proliferation of glioblastoma cells via cell cycle arrest and apoptosis

Abstract: Glioblastoma is the most common and most malignant primary brain tumor with a median survival of 15 months. Moschamine is an indole alkaloid that has a serotoninergic and cyclooxygenase inhibitory effect. In this study, we sought to determine whether moschamine could exert cytotoxic and cytostatic effects on glioma cells in vitro. Moschamine was tested for toxicity in zebrafish. We investigated the effect of moschamine on U251MG and T98G glioblastoma cell lines. Viability and proliferation of the cells were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…Our research group has been working towards novel therapeutics of GBM, which are based on natural products. Specifically, on the basis of experimental results that include FC methodologies, we have found that difluoromethylornithine (DFMO) [ 96 ] as well as the natural substances moschamine [ 97 ], n-p-coumaroyl-serotonin [ 98 ], and deglucohellebrin [ 99 ] exhibit significant antiglioma activity in vitro and low cytotoxity in vivo, as shown in a zebrafish embryo model.…”
Section: Flow Cytometry For Study Of Anticancer Agent Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has been working towards novel therapeutics of GBM, which are based on natural products. Specifically, on the basis of experimental results that include FC methodologies, we have found that difluoromethylornithine (DFMO) [ 96 ] as well as the natural substances moschamine [ 97 ], n-p-coumaroyl-serotonin [ 98 ], and deglucohellebrin [ 99 ] exhibit significant antiglioma activity in vitro and low cytotoxity in vivo, as shown in a zebrafish embryo model.…”
Section: Flow Cytometry For Study Of Anticancer Agent Efficacymentioning
confidence: 99%
“…DNA content analysis revealed several mechanisms of action for different antiglioma agents. For example, N-(p-coumaroyl)-serotonin resulted in both S and G2/M phase arrest, moschamine resulted mostly in S phase arrest and deglucohellebrin in G2/M phase arrest [ 97 , 98 , 99 ]. Several other studies have used in DNA content analysis quantification in several CNSM treatments, revealing, among others, the antiglioma effects of curcumin [ 100 ], quercetin [ 101 ], glycyrrhizic acid [ 102 ], and palbociclib [ 103 ].…”
Section: Flow Cytometry For Study Of Anticancer Agent Efficacymentioning
confidence: 99%
“…Most of the biological characteristics such as proliferation, apoptosis, and drug screening, among others, have been evaluated in vitro using cell lines [ 70 , 107 , 108 , 109 , 110 , 111 , 112 ]. Although they have been instrumental in understanding tumor behavior, the mere fact of being a cell line does not represent the actual heterogeneity of a tumor sample from a patient.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of caspase-8 was quantified with the Fluorescein Active Caspase-8 Staining Kit (Abnova, Taiwan) as described previously [ 15 ]. For the assessment of the cluster of differentiation (CD) expression, specifically CD24/CD44, we used the FITC mouse anti-human CD24 (ML5), PE mouse anti-human CD24 (ML5), and FITC mouse anti-human CD44 (Leu-44) (all from BD Pharmingen) as described previously in detail [ 16 ]. Approximately 10,000 cells were seeded in 24-well plates and after 24 h were exposed to a concentration of 100 μΜ of haloperidol, for another 72 h. The cells were then dissociated by trypsinization, washed twice with PBS and in order to block Fc receptors, incubated with 10% human serum for 20 min on ice.…”
Section: Methodsmentioning
confidence: 99%